Hardware implementation of a software radio receiver in the universal software radio peripheral using the CC1000 COTS Transceiver Module as RF front-end - Figueroa, Francis Z. (2007)
Software defined radio (SDR) is a transceiver wherein the radio operations are implemented in a general-purpose software-reconfigurable hardware. This emerging radio architecture could be the answer to the interoperability issue brought about by the numerous wireless standards (GSM, CDMA, WCDMA, AMPS, DAMPS, PDC) currently deployed in different parts of the world. With SDR technology, a single handset could be used worldwide by only downloading the appropriate configuration in a certain region. Reconfiguration and adaptability are the key features of SDRs. Since only the software is altered, SDR devices need not be replaced when new technologies come or when new service upgrades are released. A simple software defined FSK receiver was synthesized and implemented in the Universal Software Radio Peripheral (USRP). 8987 out of 12060 or 75% of the logic elements available in the Altera EPIC12 Q240C8 Cyclone FPGA of the USRP was used. An analog RF front-end (COTS/CC1000) receives the RF signal and is configured to output the signal in its intermediate frequency stage. This 10.7MHz IF signal is then digitized by the USRP's ADC, downconverted to baseband, and demodulated to output the received bits. A PC running GNURadio software was used to display the received bits from the USRP.